Strongly (001) Oriented Bimorph PZT Film on Metal Foils Grown by rf‐Sputtering for Wrist‐Worn Piezoelectric Energy Harvesters. (20th July 2018) - Yeo, Hong Goo; Xue, Tiancheng; Roundy, Shad; Ma, Xiaokun; Rahn, Christopher; Trolier‐McKinstry, Susan
Abstract: For piezoelectric energy harvesters, a large volume of piezoelectric material with a high figure of merit is essential to obtain a higher power density. The work describes the growth of highly (001) oriented sputtered lead zirconate titanate (PZT) films ( f ≈ 0.99) exceeding 4 µm in thickness on both sides of an Ni foil to produce a bimorph structure. These films are incorporated in novel wrist‐worn energy harvesters (<16 cm 2 ) in which piezoelectric beams are plucked magnetically using an eccentric rotor with embedded magnets to implement frequency up‐conversion. The resulting devices successfully convert low‐frequency vibration sources (i.e., from walking, rotating the wrist, and jogging) to higher frequency vibrations of the PZT beams (100–200 Hz). Measured at resonance, six beams producing an output of 1.2 mW is achieved at 0.15 G acceleration. For magnetic plucking of a wrist‐worn nonresonant device, 40–50 µW is produced during mild activity. Abstract : Thick piezoelectric bimorphs are used to create wrist‐worn harvesters. Beams are plucked magnetically using an eccentric rotor with embedded magnets to implement frequency up‐conversion from low‐frequency vibration sources (i.e., from walking, rotating the wrist, and jogging) to higher frequency vibrations of the lead zirconate titanate beams (100–200 Hz). The devices generate 40–50 µW power during mild activity.